PERUBAHAN TUTUPAN HUTAN DI KABUPATEN PASER, KALIMANTAN TIMUR : PENJELASAN DARI PENDEKATAN KELEMBAGAAN - Retno Maryani; Satria Astana (Jurnal Analisis Kebijakan Kehutanan, 2016)
This study has been done by using institutional approach, with the aims is to study forests cover change in Paser Regency, East Kalimantan. The collected data was consisted ofquantitative and qualitative data. The quantitative data was used to analyze the land cover changes from forested land to be non-forested land. The qualitative data was collected through interviews with snowballing method. The results showed that the forest cover in Paser Regency both located in forest area and in other areas had been transformed into a landscape with a variety ofcover types, such as: shrubs, settlements, swamps, ponds, farming, agriculture, vacant land, and mining. Three factors caused the changes in such forest cover, namely: (1) the development ofinvestment-based land resources, (2) the existence oftransactional politics that makes the forest as goods to be transacted for various interests, and (3) the chaotic situation offorest management with the openess of organization networking in the community. In order to reduce the on-going excessive forest conversion, the results ofthe study suggest that both central and local governments together need to immediately enforce the property rights over the remaining forest resources.